Acceptor‐Doping Accelerated Charge Separation in Cu2O Photocathode for Photoelectrochemical Water Splitting: Theoretical and Experimental Studies. Issue 42 (13th July 2020) - Zhang, Mengmeng; Wang, Jiajun; Xue, Hui; Zhang, Jinfeng; Peng, Shengjie; Han, Xiaopeng; Deng, Yida; Hu, Wenbin
Abstract: Cu2 O is a typical photoelectrocatalyst for sustainable hydrogen production, while the fast charge recombination hinders its further development. Herein, Ni 2+ cations have been doped into a Cu2 O lattice (named as Ni‐Cu2 O) by a simple hydrothermal method and act as electron traps. Theoretical results predict that the Ni dopants produce an acceptor impurity level and lower the energy barrier of hydrogen evolution. Photoelectrochemical (PEC) measurements demonstrate that Ni‐Cu2 O exhibits a photocurrent density of 0.83 mA cm −2, which is 1.34 times higher than that of Cu2 O. And the photostability has been enhanced by 7.81 times. Moreover, characterizations confirm the enhanced light‐harvesting, facilitated charge separation and transfer, prolonged charge lifetime, and increased carrier concentration of Ni‐Cu2 O. This work provides deep insight into how acceptor‐doping modifies the electronic structure and optimizes the PEC process. Abstract : Taking charge : A nickel (Ni) electron acceptor has been successfully doped into a Cu2 O lattice without forming impurity phases. Both theoretical and experimental results demonstrate that Ni dopants attract electrons from neighboring atoms, therefore facilitating charge separation and transfer. Consequently, the obtained Ni‐Cu2 O exhibits a significantly enhanced photoelectrochemical performance.